PARADIGMA PERAN DEKAN IDEAL: The Dove, The Dragon, dan The Diplomat dalam Membangun Fakultas yang Kuat - Abdul Kadir (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2010)
The management of a faculty should encourage staff participation for a change. A decreasing trend of government financial support for higher education pushes a faculty to be more efficient in financial plan. In line with this, a good faculty should develop harmonious relationship internally and externally. Such is a strong collaboration which may lead to positive process, input, output and outcome. To get a maximum outcome, there are at least five aspects to strengthen; strengthening of steering core, building network, developing resources, diversifying funding base, and developing a culture of entrepreneurship. To achieve these aspects, a dean should play roles as a dove, a dragon and as a diplomat.